Suspected Doxycycline Induced Acute Interstitial Nephritis - Abrahamian, Andrew; Burmeister, Cameron; Hejeebu, Srini (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF To see the formatted meeting abstract.